Acúmulo de matéria seca e de nutrientes em plantas de cobertura do solo e meloeiro em sistemas de cultivo - Silva, Antonia Rosimeire da Cruz (Universidade Federal Rural do Semi-Árido, 2015)
The objective of this work was to evaluate the dry matter production and accumulation of macronutrients, C and C / N ratio of roofing plants in the semiarid region and the growth and accumulation of nutrients in melons in different cropping systems. The experiments were conducted between April and September / October and December 2011 and between May and October / November 2012 and January 2013, in Fazenda Agrícola Famosa Ltda., located on the border of the municipalities Tibau-RN / Icapuí-CE. In the first semester, we used a randomized complete block design with five treatments and four replications. The treatments consisted of covers: sunn hemp and millet; corn + Brachiaria; spontaneous vegetation; Single millet and pork + millet beans. In the first semester, the production of dry matter of shoots of cover crops, accumulation of nutrients, carbon and C / N ratio were evaluated. In the second semester, we used the randomized block design with nine treatments and four replications. The treatments consisted of covers: Sunnhemp + embedded millet; Corn + embedded brachiaria; Embedded spontaneous vegetation; Millet not incorporated; Sunnhemp + millet not incorporated; Corn + Brachiaria not incorporated; Unincorporated spontaneous vegetation; Solo kept without vegetation unincorporated and millet + jack bean unincorporated. The greatest productions of total dry matter accumulation of macronutrients, except S and carbon, were obtained with sunnhemp + millet and corn + Brachiaria and spontaneous vegetation. Pearl millet (2011) and corn + Brachiaria and spontaneous vegetation (2012) showed higher C / N. The maximum accumulated plant dry matter in melon was observed in sunnhemp + embedded millet, sunnhemp + unincorporated millet and maize + embedded brachiaria at 30 DAT, DAT 60 and DAT 60 fruit, respectively. Embedded vegetation cover and under the mulching resulted in higher overall productivity in melon. The cover crops corn + Brachiaria and sunn hemp and millet incorporated under mulching achieved the highest business productivity in 2011 and 2012, respectively. The plant covers that contributed most to the total accumulation of N, P and K in melon were sunnhemp + embedded millet and corn + Brachiaria not incorporated
Accumulation of dry matter and nutrients in the soil cover crops and melons in cropping systems
Keywords: Melon; cover crops; Cucumis melo L .; biomass; Macronutrients - accumulation; Melão; Coberturas vegetais; Cucumis melon L.; Fitomassa; Macronutrientes - acúmulo; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA